KUALITAS AIR BERDASARKAN UJI KANDUNGAN KLOROFIL-a DI SUNGAI TUTUPAN KECAMATAN JUAI KABUPATEN BALANGAN - Aditya Rahman; Sasi Gendro Sari; Beby Rahmayanti (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2015)
This research was done to explain the status of the Tutupan River by measuring chlorophyll-a and determining the relation between chlorophyll-a and physical-chemical factors. Purposive sampling method was used to determine water sampling, the measurement of enviromental factors as temperature, water velocity, water clarity, pH and DO, meanwhile parameters as TSS, BOD5, nitrate, nitrite, orthophosphate, was measured in laboratory. Analysis of chlorophyll-a was content used a spectrophotometer. Water samples were taken twice only at April and May, 2014. The results showed the amount of chlorophyll-a in April ranged between 0,13 and 0,77 mg / m³ and in May, it ranged from 0,02 and 0,08 mg / m³. Status of the Tutupan River quality are classified as oligotrofic or low fertility rates with chlorophyll-a content ranged from 0,02 to 0,77 mg / m³. The chlorophyll-a content only closely related to the water temperature in May, with correlatin factor 0,9.